Evaluation of Factors and Biological Parameters of the Groundwater in Makasar Subdistrict, East Jakarta - Diinii Haniifah; Tri Edhi Budhi Soesilo; Dwi Nowo Martono (Universitas Airlangga, 2023)
Introduction: People prefer to use groundwater for daily needs to piped water in Indonesia. However, population growth and the construction of residential homes can hugely affect the quality of groundwater. The study aims to examine the relationship between groundwater quality and its influencing factors. Methods: This study was conducted with a quantitative approach and a survey method. Primary and secondary data were required in this study. The variables examined in this study were groundwater quality as seen from its biological parameters and influencing factors which consisted of internal and external factors. Results and Discussion: The results show that the highest coliform bacteria content was found in Cipinang Melayu at 200 MPN/100 mL concentrations in 2019 and 2020, as well as 100 MPN/100 mL in 2021, followed by Pinang Ranti. The highest coliform content was discovered in Halim Perdana Kusuma well number 3 at 50 MPN/100 mL concentration. Groundwater contains coliform because of internal influencing factors as well as external factors. Coliform content and its influence factors were both significantly correlated with a P-value < 0.05 (correlation coefficient = 0.201 for internal factors; correlation coefficient = -0.144 for external factors). The groundwater quality and internal factors were correlated with a correlation coefficient of 0.634; meanwhile, the groundwater quality was significantly correlated with external factors with a correlation coefficient of 0.656. Conclusion: Groundwater quality was not aligned with standards for drinking water as evaluated from the biological parameters. Both internal and external factors influence the Total coliform content.